The Risk of Venous Thromboembolism Attributed to Established Prothrombotic Genotypes - Evensen, Line H.; Arnesen, Carl Arne Løchen; Rosendaal, Frits R.; Gabrielsen, Maiken E.; Brumpton, Ben M.; Hveem, Kristian; Hansen, John-Bjarne; Brækkan, Sigrid K. (Thrombosis and Haemostasis, 2022)
Background The proportion of venous thromboembolism (VTE) events that can be attributed to established prothrombotic genotypes has been scarcely investigated in the general population. We aimed to estimate the proportion of VTEs in the population that could be attributed to established prothrombotic genotypes using a population-based case-cohort.Methods Cases with incident VTE (n = 1,493) and a randomly sampled subcohort (n = 13,069) were derived from the Tromsø Study (1994–2012) and the Nord-Trøndelag Health (HUNT) study (1995–2008). DNA samples were genotyped for 17 single-nucleotide polymorphisms (SNPs) associated with VTE. Hazard ratios with 95% confidence intervals (CIs) were estimated in Cox regression models. Population-attributable fractions (PAFs) with 95% bias-corrected CIs (based on 10,000 bootstrap samples) were estimated using a cumulative model where SNPs significantly associated with VTE were added one by one in ranked order of the individual PAFs.Results Six SNPs were significantly associated with VTE (rs1799963 [Prothrombin], rs2066865 [FGG], rs6025 [FV Leiden], rs2289252 [F11], rs2036914 [F11], and rs8176719 [ABO]). The cumulative PAF for the six-SNP model was 45.3% (95% CI: 19.7–71.6) for total VTE and 61.7% (95% CI: 19.6–89.3) for unprovoked VTE. The PAF for prothrombotic genotypes was higher for deep vein thrombosis (DVT; 52.9%) than for PE (33.8%), and higher for those aged <70 years (66.1%) than for those aged ≥70 years (24.9%).Conclusion Our findings suggest that 45 to 62% of all VTE events in the population can be attributed to known prothrombotic genotypes. The PAF of established prothrombotic genotypes was higher in DVT than in PE, and higher in the young than in the elderly.
Keywords: venous thromboembolism; single-nucleotide polymorphisms; risk factors